PERBEDAAN PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) DAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI KELAS X MADHARASAH ALIYAH EX PGA UNIVA MEDAN TAHUN PELAJARAN 2015/2016 - Supiah Supiah; Riri Syafitri Lubis (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
The purpose of this research is to know the difference of result learningstudent mathematics taught with the Model of cooperative learning withtype of Students Teams Achievement Division (STAD) and type ofMake A Match In Class of X Madrasah Aliyah EX PGA UNIVA at.2015/2016. This research is quantitative research with the type ofexperiment research. The population is all students of class of XMadrasah Aliyah EX PGA UNIVA at 2015/2016 amounting to 99student amounting to 4 class. Instrument test used to know the resultlearn the student is multiple choice tes in the form of test of early andtest of result of learning. In this research, researcher succeed to obtain;get to test the normalitas of at experiment class 1 to assess the pre-tesgot by value LHitung = 0,172 and assess the pos-tes got by value LHitung =0,172 of while at class of Ekperimen II to assess the pre-tes got byvalue LHitung = 0,131 and assess the pos-tes of value LHitung = 0,117,later; then for the value of second LTabel of group is 0,173, meaningpopulation have normal distribution. To test the homogeneity assessthe pre-tes obtained by FHitung = 1,764 and assess the pos-tes obtained byFHitung = 1,93, while for the FTabel = 1,984 of, meaning second ofhomogeneous sampel. While to test the hypothesis t got by value ofthitung = 4,09 and ttabel = 2,011. meaning thitung>ttabel that is 4,09 > 2,011.Therefore, H0 refused and HA accepted meaning that there aredifference of result of learning student taught with the model ofcooperative learning of type student teams achievement division(STAD) with the model of study of Make A match of at items ofMathematics Logic in class of X MAS of Project Univa.